Membangun Ulang Media Cetak di Era Digital: Analisis Strategi The New York Times - Setyawan, Irwan (Universitas Brawijaya, 2025)
The collapse of the newspaper industry since 2008 has made many publishers seem to have lost their way. The concept of media convergence, which was initially considered the only way to deal with the development of internet and digital technology, has not been able to make media companies rise from the threat of death. Including the fate of newspapers in Indonesia that have not found a